Pluralitas dan Tantangannya - Mustafa Mustafa (Institut Agama Islam Negeri (IAIN) Kendari, 2008)
Theoretically, the concept of the plurality is diverse. The plurality includes both metaphysical and physical areas. In a metaphysical area especially in the field of religious faith-there is also plurality. Each is recognized for its existence in accordance with the beliefs of its adherents, both on theological, political and economic aspects.The dominant plurality challenge is the truth claim. Theological, political and economic issues are the three most important factors in life which in history have seen that the theological factor once dominated Western culture, then the political economy, the third world was dominated by the West. Even this dominance by the US, as a superpower, seems to be sustained to the present day. The dominant attitude is not in accordance with the spirit of the concept of plurality. The way of solving it in the field of da'wah is, among others, with an ethical-humanist approach on the principle of universal human values